Cervical Spinal Cord Injury with a Minor Trauma in A Patient with Ankylosing Spondylitis: A Case Report - Serpil Savaş; Erdem İlgün and Aşkın Görgülü and Ahmet Yeşildağ (Archives of Rheumatology, 2008)
Patients with advanced ankylosing spondylitis are prone to fractures of cervical spine following minor injuries. In this case report, we present a case of ankylosing spondylitis where the patient sustained cervical spinal cord injury after a minor traffic accident. (Rheumatism 2008 23: 28-30)